Molecular and Functional Characterization of Odorant Binding Protein 7 From the Oriental Fruit Moth Grapholita molesta (Busck) (Lepidoptera: Tortricidae) - Chen, Xiu-Lin; Li, Guang-Wei; Xu, Xiang-Li; Wu, Jun-Xiang (Frontiers in Physiology, 2018)
Odorant-binding proteins (OBPs) are widely and abundantly distributed in the insect sensillar lymph and are essential for insect olfactory processes. The OBPs can capture and transfer odor molecules across the sensillum lymph to odorant receptors and trigger the signal transduction pathway. In this study, a putative OBP gene, GmolOBP7, was cloned using specific-primers, based on the annotated unigene which forms the antennal transcriptome of Grapholita molesta. Real-time PCR (qRT-PCR) analysis revealed that GmolOBP7 was highly expressed in the wings of males and the antennae of both male and female adult moths, while low levels were expressed in other tissues. The recombinant GmolOBP7 (rGmolOBP7) was successfully expressed and purified via Ni-ion affinity chromatography. The results of binding assays revealed that rGmolOBP7 exhibited a high binding affinity to the minor sex pheromone 1-dodecanol containing Ki of 7.48 μM and had high binding capacities to the host-plant volatiles, such as pear ester, lauraldehyde and α-ocimene. RNA-interference experiments were performed to further assess the function of GmolOBP7. qRT-PCR showed that the levels of mRNA transcripts significantly declined in 1 and 2 day old male and female moths, treated with GmolOBP7 dsRNA, compared with non-injection controls. The EAG responses of dsRNA-injected males and females to pear ester, as well as the EAG responses of dsRNA-injected males to 1-dodecanol, were significantly reduced compared to the GFP-dsRNA-injected and non-injected controls. We therefore infer that GmolOBP7 has a dual function in the perception and recognition of the host-plant volatiles and sex pheromones.